A sandwich-like configuration with a signal amplification strategy using a methylene blue/aptamer complex on a heterojunction 2D MoSe2/2D WSe2 electrode: Toward a portable and sensitive electrochemical alpha-fetoprotein immunoassay - Chanarsa, Supakeit; Jakmunee, Jaroon; Ounnunkad, Kontad (Frontiers in Cellular and Infection Microbiology, 2022)
Liver cancer is one of the most common global health problems that features a high mortality rate. Alpha-fetoprotein (AFP) is a potential liver cancer biomarker for the diagnosis of liver cancer. The quantitative detection of AFP at an ultratrace level has important medical significance. Using the reaction of the antibody–antigen pair in an immunosensor enables the sensitive and selective AFP assay. Finding a strategy in signal generation and amplification is challenging to fabricate new sensitive electrochemical immunosensors for AFP detection. This study demonstrates the construction of a simple, reliable, and label-free immunosensor for the detection of AFP on a smart phone. Exfoliated two-dimensional (2D) molybdenum diselenide (MoSe2) and 2D tungsten diselenide (WSe2) were employed to modify the disposable screen-printed carbon electrode (SPCE) to use as the electrochemical platform, which is affixed to a small potentiostat connected to a smart phone. The modified electrode offers antibody immobilization and allows detection of AFP via an immunocomplex forming a sandwich-like configuration with the AFP-corresponding aptamer. A heterojunction 2D MoSe2/2D WSe2 composite improves the SPCE’s reactivity and provides a large surface area and good adsorption capacity for the immobilizing antibodies. The signal generation for the immunosensor is from the electrochemical response of methylene blue (MB) intercalating into the aptamer bound on the electrode. The response for the proposed sandwich-like immunosensor is proportional to the AFP concentration (1.0–50,000 pg ml-1). The biosensor has potential for the development of a simple and robust point-of-care diagnostic platform for the clinical diagnosis of liver cancer, achieving a low limit of detection (0.85 pg ml-1), high sensitivity, high selectivity, good stability, and excellent reproducibility.